Experimental demonstration of single flux quantum logic with resettable latch. - Furuta, F. (IEEE Transactions on applied superconductivity)
We report experimental demonstrations of logic functions based on single flux quantum logic with resettable latch (SFQ-RL) logic. SFQ-RL has been proposed as new SFQ logic, which enables us to initialize the whole circuit. This initialization function is essential for the state machine into which conventional SFQ logic is classified, and makes SFQ logic more applicable to a large-scale logic system, such as a processor. In addition, the function can prevent circuits from performing the failed operation caused by a trapped flux in storage loops. The logic consists of three primitives, which can compose any logic function. We have experimentally demonstrated the operation of ?half adder? based on SFQ-RL with the bias margin of ±16%. In order to examine the function of initialization, we designed and evaluated a pseudo random sequence generator by numerical simulation. In addition, we experimentally confirmed the initialization of the generator and ?circular buffer? with the bias margin of ±20%